Optimization of Making Edible Film from Glucomannan Flour with the Addition of CaCO3, Gelatin, Glycerol, Coconut Oil, and Tea Tree Oil - Zakijah Irfin; Dwina Moentamaria; Anugraheni Nur Arifa (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
The increase in population causes the level of basic needs to increase, one of which is in terms of food. Where mostly, the food industry uses petroleum-based plastic packaging, the use of these materials can contaminate food due to the nature of the chemical substances that are easily mixed with the packaged products. Therefore, it is necessary to have packaging technology that is safe and does not damage the environment, for example edible film (McHugh and Krochta 1994). The process of making edible films is carried out by mixing the independent variables, namely the concentration of CaCO3, gelatin, coconut oil, and glycerol and then testing the product in the form of tensile strength, elongation, water vapor transmission rate, and thickness. The first objective of this study is to determine the effect of each independent variable on tensile strength, elongation, water vapor transmission rate, thickness, biodegradation, and the number of microbes. Second, obtaining the optimum composition through RSM. The optimum results obtained from RSM resulted in the composition of each variable and response, namely gelatin 7 grams, CaCO3 0.8 grams, coconut oil 3 ml, and glycerol 2 ml and resulted in a minimum thickness response of 0.1 mm, minimum water vapor transmission rate of 1 g.m2 /day, maximum tensile strength of 86 kgf/cm2 , and maximum elongation of 43%.